2020
DOI: 10.1007/s00262-020-02544-5
|View full text |Cite|
|
Sign up to set email alerts
|

Human ovarian cancer intrinsic mechanisms regulate lymphocyte activation in response to immune checkpoint blockade

Abstract: Immune checkpoint blocking antibodies are currently being tested in ovarian cancer (OC) patients and have shown some responses in early clinical trials. However, it remains unclear how human OC cancer cells regulate lymphocyte activation in response to therapy. In this study, we have established and optimised an in vitro tumour-immune co-culture system (TICS), which is specifically designed to quantify the activation of multiple primary human lymphocyte subsets and human cancer cell killing in response to PD-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 33 publications
(41 reference statements)
0
19
0
Order By: Relevance
“… 34 Treatment of cancer cell lines with DNMTi alone or in combination with HDACi resulted in upregulation of MICA and MICB, which resensitized tumor cells to NK cell attack in vitro . 35–37 Furthermore, we and others have previously shown DNMTi-induced upregulation of immunoregulatory genes, including HLA and PD-L1 10 38 ; such upregulation is likely another key factor, beside ERV and IFN I induction, governing the observed enhanced immune cell killing of DNMTi-treated tumor cell lines in vitro .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“… 34 Treatment of cancer cell lines with DNMTi alone or in combination with HDACi resulted in upregulation of MICA and MICB, which resensitized tumor cells to NK cell attack in vitro . 35–37 Furthermore, we and others have previously shown DNMTi-induced upregulation of immunoregulatory genes, including HLA and PD-L1 10 38 ; such upregulation is likely another key factor, beside ERV and IFN I induction, governing the observed enhanced immune cell killing of DNMTi-treated tumor cell lines in vitro .…”
Section: Discussionmentioning
confidence: 73%
“…Pretreatment with epigenetic therapy has emerged as a potential strategy to stimulate immunologically cold tumors, including EOC, toward a less immunosuppressive and immune ‘evasive’ phenotype. 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…Indeed the modulation of PD-L1 expression has been reported to be affected by the extracellular matrix stiffness of tumors in 3D culture (207) and a 3D model system utilizing patient-derived organoids that resembled the tumor immune microenvironment for the study of the PD-1/PD-L1 signaling axis has been developed (208). Furthermore, in a recent study a tumor-immune co-culture was utilized to assess the efficacy of immunotherapies Nivolumab and Durvalumab (209).…”
Section: Future Direction "Modeling Tumor Heterogeneity" To Further Ementioning
confidence: 99%
“…In addition to BCL3, Guo et al discovered that dinaciclib, a cyclin-dependent kinase (CDK) inhibitor, induced PD-L1 and PD-L2 levels on TILs, forming the hypothesis that targeting CDKs could potentially improve EOC patient immunotherapeutic response [ 121 ]. A recent study by Natoli et al used a sophisticated in vitro tumor-immune co-culture system (TICSs) consisting of ovarian cancer cells and EOC patient ascites and observed that ovarian cancer chemoresistant cells had overall low levels of human leukocyte antigen (HLA) contributing to a poor response to nivolumab monotherapy [ 122 ]. To enhance nivolumab response, the authors found that HLA could be induced by a DNA methyltransferase inhibitor, providing a potential method to enhance patient response to PD-1 blockade [ 122 ].…”
Section: Pd-1 Based Combinatorial Approachesmentioning
confidence: 99%
“…A recent study by Natoli et al used a sophisticated in vitro tumor-immune co-culture system (TICSs) consisting of ovarian cancer cells and EOC patient ascites and observed that ovarian cancer chemoresistant cells had overall low levels of human leukocyte antigen (HLA) contributing to a poor response to nivolumab monotherapy [ 122 ]. To enhance nivolumab response, the authors found that HLA could be induced by a DNA methyltransferase inhibitor, providing a potential method to enhance patient response to PD-1 blockade [ 122 ]. Finally, it was also found that inhibition of histone deacetylase (HDAC) via romidepsin along with IFNγ induces PD-L1 expression [ 123 ].…”
Section: Pd-1 Based Combinatorial Approachesmentioning
confidence: 99%